Identifikasi Ketersediaan dan Kualitas Sarana Prasarana Lingkungan di Urban Fringe Area Kelurahan Pudakpayung - Ajeng Dwi Handayani; Nany Yuliastuti (Jurnal Wilayah dan Lingkungan, 2014)
Pudakpayung Sub District is the southest in Banyumanik District of Semarang City. This area is a Urban Fringe Area with high population growth and development area for human settlement. But not supported by good facilities and infrastructure. This research is aiming to see the availability and quality of facilities and infrastructure in this urban fringe area. So, this research can give the recommendation about availability and quality of facilities and infrastructure, especially in urban fringe area. This research will identify changes the pattern of human settlement and then identify the availability, quality, and distribution of neighborhoods facilities and infrastructure. The research method used in this research is quantitative descriptive method. The analysis uses the quantitative descriptive analysis with the provisions of SNI 03-1733-2004, scoring with a Likert scale, and spatial mapping. The result of this research indicate changes the pattern of land up and indicate the availability, quality, and distribution of every facilities and infrastructure.